Advances in immunology. - Dixon, Frank J. (Frank James), 1920-2008; Alt, Frederick W. (Advances in immunology., 2002)
Advances in Immunology presents current developments as well as comprehensive reviews in immunology. Articles in this volume address topics such as protein degradation and the generation of MHC class I-presented peptides, proteolysis and antigen presentation by MHC Class II molecules, cytokine memory of T-helper lymphocytes, Ig gene hypermutation, generalization of single immunological experiences by idiotypically mediated clonal connections, and aging of the immune system. Edited and authored by the foremost scientists in the field, each volume provides up-to-date information and directions f.